"Holocaust Laughter"? A German response to Punch Me In the Stomach - Oldenhage, Tania (The journal of religion and film, 1997)
Punch Me in the Stomach is the story of Deb Filler, the daughter of a concentration camp survivor. It is, in fact, an adaptation of comedienne Filler's one woman stage show, in which she plays the role of 36 different characters from her extended family. In the story, Deb is asked by her father to accompany him on a tour of the camps in which he was incarcerated during the Holocaust. She tells of this experience, but only after telling a wide range of other stories about her own family and growing up. I [Tania Oldenhage] first saw Punch Me in the Stomach because it was recommended by a friend of mine who is working on second-generation writers of the Holocaust.